2018
DOI: 10.1007/s00431-018-3300-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional management of young infants presenting with acute bronchiolitis in Belgium, France and Switzerland: survey of current practices and documentary search of national guidelines worldwide

Abstract: Social cues, such as eye gaze and pointing fingers, can increase the prioritisation of specific locations for cognitive processing. A previous study using a manual reaching task showed that, although both gaze and pointing cues altered target prioritisation (reaction times [RTs]), only pointing cues affected action execution (trajectory deviations). These differential effects of gaze and pointing cues on action execution could be because the gaze cue was conveyed through a disembodied head; hence, the model la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Sochet et al reported that oral nutrition in infants with bronchiolitis was well tolerated and that the nasogastric tube was required for infants with higher RR 17 , and other studies have shown the difficulty with feeding and changes in swallowing that can occur among infants with bronchiolitis, showing that interference of respiratory discomfort can affect the efficacy of suction and the swallowing process 23,24 . Therefore, the need for a nasogastric tube may be a marker of the severity of respiratory distress.…”
Section: Discussionmentioning
confidence: 99%
“…Sochet et al reported that oral nutrition in infants with bronchiolitis was well tolerated and that the nasogastric tube was required for infants with higher RR 17 , and other studies have shown the difficulty with feeding and changes in swallowing that can occur among infants with bronchiolitis, showing that interference of respiratory discomfort can affect the efficacy of suction and the swallowing process 23,24 . Therefore, the need for a nasogastric tube may be a marker of the severity of respiratory distress.…”
Section: Discussionmentioning
confidence: 99%
“…Many early guidelines recommended avoiding or limiting enteral nutrition in respiratory distress (American Bronchiolitis Guidelines), however NIV is no longer a barrier to enteral feeding, in accordance with recent updated guidelines (22).…”
Section: Discussionmentioning
confidence: 90%
“…Although these events are rare, 23,24 disparate practices exist both regionally and by provider, including timing, route, and type of EN. 25,26 For children, a state of bad temperament or irritability from hunger, sometimes referred to as "hanger," 27 may anecdotally mimic respiratory distress or generate alarming vital signs that prolong LOS. 27 It remains unclear if EN is therapeutic by promoting coping and soothing during NIV.…”
mentioning
confidence: 99%